COVID-19 in Papua New Guinea - Economic and Social Impacts : Insights from the Fourth Round of High Frequency Phone Surveys - Data Collected in December 2021 (Washington, DC: World Bank, 2022)
This report focuses on the socio-economic impacts of Coronavirus (COVID-19) in Papua New Guinea. The report shows insights from the fourth round of high frequency phone surveys conducted as of December 2021. Economic recovery was weak with household incomes falling. Low vaccination rates may further hinder recovery and welfare outcomes.